Gambaran Saturasi Oksigen dan Respiratory Rate pada Pasien Penyakit Paru Obstruktif Kronis: Descriptive Oxygen Saturation and Respiratory Rate in Chronic Obstructive Pulmonary Disease - Sofiana, Zulia sofiana; Melastuti, Erna (Jurnal Keperawatan Berbudaya Sehat, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a condition that involves structural changes or scarring in the airways, leading to persistent inflammation that can hinder oxygen delivery through alveolar damage and respiratory physiological changes. These damages and changes result in symptoms such as shortness of breath, increased respiratory rate, limited lung movement, and excessive sputum production, as well as hindering the ciliary clearance process, causing sputum accumulation, and preventing effective airway clearance. The study aims to determine the oxygen levels and respiratory rate in COPD patients. The research approach is descriptive quantitative with a sample of 87 COPD patients treated at RS Awal Bros Bagan Batu. The research was conducted from November to December 2024, taking into account the results of blood gas analysis and calculating the respiratory rate using laboratory methods. The analysis used is univariate analysis. The survey results indicate that the majority of respondents (90-95%) experienced mild hypoxia, with 64 (73.6%) out of a total of 87 respondents (100%) experiencing mild hypoxia. The respiratory rate (RR) results show that 87 out of 87 subjects (100%) experienced tachypnea with a respiratory rate >20 times/minute.